Determination of form factor for oriental beech (Fagus orientalis Lipsky) in Golestan province - Mohammad Reza Kordi; Jahangir Mohammadi; Mohammad Hadi Moayyeri; Jahanbakhsh Sadeghian (تحقیقات جنگل و صنوبر ایران, 2017)
Oriental beech (Fagus orientalis Lipsky) is one of the most valuable tree species that covers 17.6% of the area and make up 30% of the stand volume in the Hyrcanian forests. This study aimed to update the form factor and to improve the volume table of this species. For this purpose, we applied random sampling method to collect field data from 150 beech trees in different diameter at breast height (D.B.H) classes (30-135 cm) based on inventory and marking list of 2015-2016. The sample trees were distributed in five forest management plan area including Livan, Vatana, Kordkuy, Shamushak, and Dr. Bahramnia. In each tree, D.B.H and diameter at 0.1, 0.3, 0.5, 0.7 and 0.9 of tree height, as well as diameter at two tops of 2 m long logs were measured. Finally the tree volume, true, natural, artificial and Hohnadl form factor for each tree was computed. The results showed that true, natural, artificial, and Hohnadl form factor value were 0.503, 0.464, 0.407 and 0.454, respectively. There were significant statistical differences between the true, artificial and natural with Hohnadl form factor (α = 0.05). The difference between true and natural form factor was not significant. Also, the results showed that there was significant difference between the computed volume and the volume driven from volume table (tariff); the greatest differences between the mentioned volumes estimated was mainly in the large D.B.H classes. According to the results, we can conclude that the natural form factor can be applied to determine the beech form factor.